Controversies of the Implementation of Carbon Tax Policy for the Australian Economy: Harmful or Beneficial? - Nur Arif Nugraha (Andalas Journal of International Studies (AJIS), 2017)
Australian government had an experience in carbon tax policy implementation and evidently, it did not work out since it was enacted for the first time in 2012. The background of this policy was the Kyoto Protocol in 2007. In the beginning, Australia and United States considered as resistant countries. However, the government finally implemented carbon tax policy in 2012. There were many debates around this issue, especially two major parties, Labour and Liberal. After some considerations, the Australian government decided to repeal this policy in 2014. This study will focus on controversies around the implementation of carbon tax policy. The first part will describe the background of carbon tax policy. The next part will expose on positive impacts of the policy implementation on the Australian economy, while the following part will focus on negative impacts on household expenditures. The final part will conclude which actions the government should decide either continues or terminates carbon tax policy.  Keywords: implementation, carbon tax policy, environment, household, economy